2012
DOI: 10.1016/j.physbeh.2012.02.022
|View full text |Cite
|
Sign up to set email alerts
|

Delaying orthostatic syncope with mental challenge: A pilot study

Abstract: At orthostatic vasovagal syncope there appears to be a sudden decline of sympathetic activity. As mental challenge activates the sympathetic system, we hypothesized that doing mental arithmetic in volunteers driven to the end point of their cardiovascular stability may delay the onset of orthostatic syncope. We investigated this in healthy male subjects. Each subject underwent a head up tilt (HUT)+ graded lower body negative pressure (LBNP) up to presyncope session (control) to determine the orthostatic tolera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
18
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 24 publications
(33 reference statements)
1
18
0
Order By: Relevance
“…To sum up, this holistic analysis showed that MAP is the most salient variable to predict failure to complete the experiment. This is in agreement with the observation that blood pressure is a primarily related variable during stress application, as was reported first by Julius (Julius 1991) and confirmed in subsequent studies (Goswami et al 2010, 2011, 2012; Patel et al 2016). …”
Section: Discussionsupporting
confidence: 92%
“…To sum up, this holistic analysis showed that MAP is the most salient variable to predict failure to complete the experiment. This is in agreement with the observation that blood pressure is a primarily related variable during stress application, as was reported first by Julius (Julius 1991) and confirmed in subsequent studies (Goswami et al 2010, 2011, 2012; Patel et al 2016). …”
Section: Discussionsupporting
confidence: 92%
“…We have also previously reported that mental challenge–induced increases in sympathetic activity could lead to improvements in orthostatic tolerance times in subjects undergoing graded lower body negative pressure until presyncope. 21 …”
Section: Discussionmentioning
confidence: 99%
“…In addition to reviewing the state of the art knowledge regarding orthostatic intolerance, this review also examines specific countermeasures that can be used against orthostatic intolerance. For instance, orthostatic tolerance has been shown to be improved by exercise (Howden et al, 2004 ), water drinking (Schroeder et al, 2002 ), and mental arithmetic (Goswami et al, 2012a ). Other countermeasures that could potentially prevent or mitigate orthostatic intolerance can include simple measures such as standing up slowly (de Bruïne et al, 2017 ) and/or compression of abdominal region (Figueroa et al, 2010 ).…”
Section: Introductionmentioning
confidence: 99%